2010
DOI: 10.1007/s00204-010-0574-0
|View full text |Cite
|
Sign up to set email alerts
|

Aspect ratio has no effect on genotoxicity of multi-wall carbon nanotubes

Abstract: Carbon nanotubes (CNTs) have specific physico-chemical and electrical properties that are useful for telecommunications, medicine, materials, manufacturing processes and the environmental and energy sectors. Yet, despite their many advantages, it is also important to determine whether CNTs may represent a hazard to the environment and human health. Like asbestos, the aspect ratio (length:diameter) and metal components of CNTs are known to have an effect on the toxicity of carbon nanotubes. Thus, to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 33 publications
0
43
1
Order By: Relevance
“…The general expectation is that CNTs will be applied to many industrial fields, such as oil filters, mobile phones, aircraft, sporting goods, and drugs, because of their electrical conductivity, mechanical strength, and thermal conductivity (Murphy 2002;Gooding et al 2003;Lin et al 2004;Kim et al 2011). However, along with the increasing use of CNTs, there is also an increased potential for exposure (Maynard et al 2004;Reddy et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general expectation is that CNTs will be applied to many industrial fields, such as oil filters, mobile phones, aircraft, sporting goods, and drugs, because of their electrical conductivity, mechanical strength, and thermal conductivity (Murphy 2002;Gooding et al 2003;Lin et al 2004;Kim et al 2011). However, along with the increasing use of CNTs, there is also an increased potential for exposure (Maynard et al 2004;Reddy et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CNTs induce reactive oxygen species (ROS) generation, immune suppression, and pulmonary fibrosis that is associated with an increased risk of lung cancer (Hubbard et al 2000;Knaapen et al 2004;Pulskump et al 2007;Mitchell et al 2007;Shvedova et al 2009). Other studies found that CNTs induced DNA damage in an in vitro micronuclei assay and caused cytotoxicity, yet not genotoxicity in in vitro and in vivo tests (Karlsson et al 2008;Lindberg et al 2009;Kim et al 2010Kim et al , 2011. In addition, CNTs have been reported to activate gene expression related to oxidative stress response, cellular transport, metabolism, and cell cycle regulation in in vivo and in vitro systems (Chui et al 2005;Ding et al 2005;Manna and Ramesh 2005;Mitchell et al 2007;Sarkar et al 2007;Chou et al 2008;Poma and Di Giorgio 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This review discussed the current possibilities and perspectives of in vitro test systems for nanotoxicology (36) Clift et al (2011) The aspect ratio (defined as the ratio length: diameter) of carbon nanotubes has no influence on genotoxicity (37) Kim et al (2011) Inorganic arsenic induces apoptosis in the cerebrum of mice (38) Yen et al (2011) Increasing age leads to alterations of hepatic cytochrome P450 isoforms in rats. CYP1A1, CYP1A2, CYP2B1 and CYP2E1 were maximally expressed at 3 weeks, and then later decreased (39) Yun et al (2010) This review gives an update on the mechanisms of action and cellular targets of toxic metals, as well as the use of chelating agents for pharmaceutical treatment (40) Sinicropi et al (2010) This review summarises epidemiological studies on maternal exposure to particulate matters and adverse pregnancy outcomes.…”
Section: Key Messages Referencesmentioning
confidence: 99%
“…In recent years, the number of contributions about nanotechnology submitted to our journal has massively increased (Gibson et al 2011;Truong et al 2011;Heng et al 2011a;Jeong et al 2010). Cutting-edge topics in our journal are uptake and biodistribution (Zhang et al 2011;Gehrke et al 2011;Xie et al 2010), inflammation and apoptosis (Heng et al 2011b;Lee et al 2011;Marano et al 2011) as well as oxidative stress and genotoxicity (Foldbjerg et al 2011;Clift et al 2011;Kim et al 2011) induced by nanoparticles.…”
mentioning
confidence: 99%